Building character and culture - Hutcheon, Pat Duffy (Praeger, 1999)
This text stresses the importance of culture in human development, and the collective responsibility for the direction in which it evolves. It proceeds from exploring humans as creators and creatures of culture to the role of agents of socialization in cognitive development and character formation.